A STORY OF ONE HOUSE: Architect Artyushkov’s House - Grigoryeva, Elena (project baikal, 2015)
The article announces a selection of materials about the architect A. P. Artyushkov, who worked in Irkutsk from 1894 to 1938, and about the house designed by him, where he, his children and grandchildren lived.
Keywords: architect; Alexander Petrovich Artyushkov; Irkutsk; modern